Ibraim Goradze – a Writer and Translator - Phutkaradze, Elza; Malakmadze, Roin (BLACK SEA REGION AT THE CROSSROADS OF CIVILIZATIONS, 2025)
The work deals with the creative activities of Ibraim Goradze. He was a victim of the repressions of 1937 and spent most of his life in Turkey. His translating activity is well known to the society and scientific circles. He used to translate from Georgian into Turkish and vice versa. However, as a writer, he is still unknown. However, we have obtained his archive. It is the archive that has preserved for us his manuscript, an autobiographical work – “My Tragic Fate”. Studying this interesting work from the different prisms and, at the same time, introducing, studying, and presenting Ibraim Goradze as the author of a remarkably emotional handwriting is the goal of the research. Accordingly, the research is relevant and innovative. The work introduces us to interesting details of Ibraim’s life, work, and creative activity. Through the familiarizing ourselves with biographical details a complete portrait of the author is drawn. At the same time, without any embellishment, he boldly introduces us to the era of that time, to the extremely difficult situation in the country and its villages. He tells us how both his village and the author himself became the victims of the misfortunes and repressions of that time. It is with particular heartache that he speaks to us about impoverished human relationships. He gives the detailed description how the people of this small village find themselves part of the evils of the epoch and then sacrifice themselves for the neighbors they grew up with, and how people can be made miserable by their “good” friends, those who grew up together in the village and spent their childhood years together, because of their well-being. It is precisely the fault of such people that results in Ibrahim's “tragic fate”. All of this is described by the author without artistic or expressive means, thereby further emphasizing the intensity of the pain. Accordingly, the writing style is simple, yet with this simplicity, with a simple narrative, it deeply portrays the everyday life of his life, the darkness of the era, and gives us a glimpse into the heavy, troubled world of his soul.